Novel pyrimidine-substituted chalcones: In vitro antioxidant properties and cytotoxic effects against human cancer cell lines - Prashant Nayak; Vikram S. Shenoy; Vijay Upadhye; Kasim Sakran Abass; Omar Awad Alsaidan; Mukesh Soni; Sunil Tulshiram Hajare (PLoS ONE, 2025)
A series of novel pyrimidine-substituted chalcones were synthesized, purified, and characterized. Four selected compounds ( CFMPY 4, 15, 17, and 28 ) exhibited modest antioxidant activity across six In vitro radical scavenging assays. The In vitro cytotoxic (anticancer) potential of five synthesized chalcones ( CFMPY-2, 4, 15, 17, and 28 ) was evaluated using MTT, Sulforhodamine B (SRB), DNA fragmentation, Nuclear staining, and Farnesyl transferase assays. Notably, this study is the first to employ a DNA fragmentation assay to assess the anticancer activity of these test compounds. MTT and SRB assays revealed significant cytotoxicity in HeLa and A549 cell lines for all compounds except CFMPY 17 , with IC50 values ranging from 2.28 to 5.48 µg/ml, demonstrating comparable or superior efficacy to cisplatin (IC50 values of 5.27 µg/ml in HeLa and 4.05 µg/ml in A549 cells). Nuclear staining and DNA fragmentation assays confirmed the induction of apoptosis by all tested compounds, including cisplatin, with the latter revealing characteristic 200 bp DNA laddering. Furthermore, the Farnesyl transferase assay indicated good cytotoxic activity for all compounds except CFMPY 17 . These findings suggest that pyrimidine-substituted chalcones represent a promising class of cytotoxic (anticancer) agents, potentially exceeding the efficacy of cisplatin in certain contexts.